Silent Brain Infarcts Following Cardiac Procedures: A Systematic Review and Meta‐Analysis. Issue 9 (7th May 2019) - Indja, Ben; Woldendorp, Kei; Vallely, Michael P.; Grieve, Stuart M.
Abstract : Background: Silent brain infarcts (SBI) are increasingly being recognized as an important complication of cardiac procedures as well as a potential surrogate marker for studies on brain injury. The extent of subclinical brain injury is poorly defined. Methods and Results: We conducted a systematic review and meta‐analysis utilizing studies of SBIs and focal neurologic deficits following cardiac procedures. Our final analysis included 42 studies with 49 separate intervention groups for a total of 2632 patients. The prevalence of SBIs following transcatheter aortic valve implantation was 0.71 (95% CI 0.64‐0.77); following aortic valve replacement 0.44 (95% CI 0.31‐0.57); in a mixed cardiothoracic surgery group 0.39 (95% CI 0.28‐0.49); coronary artery bypass graft 0.25 (95% CI 0.15‐0.35); percutaneous coronary intervention 0.14 (95% CI 0.10‐0.19); and off‐pump coronary artery bypass 0.14 (0.00‐0.58). The risk ratio of focal neurologic deficits to SBI in aortic valve replacement was 0.22 (95% CI 0.15‐0.32); in off‐pump coronary artery bypass 0.21 (95% CI 0.02‐2.04); with mixed cardiothoracic surgery 0.15 (95% CI 0.07‐0.33); coronary artery bypass graft 0.10 (95% CI 0.05‐0.18); transcatheter aortic valve implantation 0.10 (95% CI 0.07‐0.14); and percutaneous coronary intervention 0.06 (95% CI 0.03‐0.14). The mean number of SBIs per patient was significantly higher in the transcatheter aortic valve implantation group (4.58 ± 2.09) compared with both the aortic valve replacement group (2.16 ± 1.62, P =0.03) and the percutaneous coronary intervention group (1.88 ± 1.02, P =0.03). Conclusions: SBIs are a very common complication following cardiac procedures, particularly those involving the aortic valve. The high frequency of SBIs compared with strokes highlights the importance of recording this surrogate measure in cardiac interventional studies. We suggest that further work is required to standardize reporting in order to facilitate the use of SBIs as a routine outcome measure.